(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This study was carried out to investigate the pathological causes of camel livers condemned at Tamboul slaughterhouse . A total of 100 condemned livers of camels at Tamboul abattoir were grossly and microscopically examined using routine H&E stain.Special stains were furtherly used to verify the lesions and identify organisms. The pathological conditions as judges macroscopically included hydatid cysts (33%), cirrhosis (15%), necrosis (13%), congestion (13%), abscess (9%), fatty changes (7%), telangiectasis&haemorrhages (5%), calcification (3%) and adhesions (2%). Histopathological examination was made to describe the microscopic picture of these conditions. Gram positive colonies of bacteria (cocci and bacilli) were demonstrated using gram’s stain in sections taken from abscesses. For demonstration of collagen fibers particularly in liver cirrhosis conditions, Van Gieson’s stain was used and the fibers were stained by deep red color.